Assessment of ball milling methodology to develop polylactide‐bacterial cellulose nanocrystals nanocomposites. Issue 10 (28th October 2014) - Ambrosio‐Martín, Jesús; Lopez‐Rubio, Amparo; Fabra, María José; Gorrasi, Giuliana; Pantani, Roberto; Lagaron, Jose María
ABSTRACT In this work, ball milling is evaluated as a methodology to develop polylactide (PLA)‐bacterial cellulose nanocrystals (BCNC) nanocomposites. This technique, widely used for clay‐based nanocomposites, is effective in breaking up to a very large extent the freeze‐dried nanocellulose aggregates, giving raise to transparent films similar to the neat PLA films. Incorporation of the nanofiller through this methodology enhances the polymer crystallinity index. An increase in the onset degradation temperature and a significant reinforcing effect in terms of an increase in the storage modulus and in the tan delta peak are also observed. Improved barrier to oxygen at high relative humidity (80%) is also noticed, reaching the best performance at the lowest BCNC loading (0.5 wt %). These improvements are related to the relatively good nanocellulose dispersion and distribution attained for low loadings of the nanofiller. Thus, the ball milling methodology appears as a feasible processing methodology for developing PLA‐BCNC nanocomposites. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41605.